2018
DOI: 10.2147/opth.s148264
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and virological analysis of epidemic keratoconjunctivitis caused by adenovirus type 54 in a regional ophthalmic clinic in Kyushu, Japan

Abstract: BackgroundHuman adenovirus type 54 (HAdV-54) is a novel type of adenovirus that belongs to species D and has thus far been detected only in Japan in patients with epidemic keratoconjunctivitis (EKC). There was a large nationwide outbreak of HAdV-54 EKC from 2015 to 2016 in Japan. The clinical characteristics of an outbreak of HAdV-54 conjunctivitis treated in a regional ophthalmic clinic in Fukuoka, Japan, in 2016 were analyzed.Patients and methodsA consecutive series of 55 cases diagnosed clinically as EKC co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…The occurrence of superficial punctate keratitis (SPK) during the acute phase of adenoviral keratoconjunctivitis and that of multiple subepithelial corneal infiltrates (MSI) during the subacute and chronic phases have been well reported. Clinical features are typically moderate in the early phase of HAdV-54 keratoconjunctivitis; however, the occurrence rate of MSI was higher than that in previous epidemics of several HAdV types [6, 7]. Uemura et al reported that the clinical severity of HAdV-54 keratoconjunctivitis was mild, moderate and severe in 3.6, 94.6 and 1.8% of cases, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of superficial punctate keratitis (SPK) during the acute phase of adenoviral keratoconjunctivitis and that of multiple subepithelial corneal infiltrates (MSI) during the subacute and chronic phases have been well reported. Clinical features are typically moderate in the early phase of HAdV-54 keratoconjunctivitis; however, the occurrence rate of MSI was higher than that in previous epidemics of several HAdV types [6, 7]. Uemura et al reported that the clinical severity of HAdV-54 keratoconjunctivitis was mild, moderate and severe in 3.6, 94.6 and 1.8% of cases, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, HAdV-8, -19 and -37 cause a more severe form of epidemic keratoconjunctivitis [5,[7][8][9][13][14][15][16][17]. In addition, epidemic keratoconjunctivitis [18][19][20] is caused by enterovirus type 70, human coxsackievirus A24 variant (CVA24v), and HAdV-11. Outbreaks caused by adenovirus types 8, 56, 54 and enteroviruses CVA24v, and EV70 have been reported in China and other countries or regions around the world [6,15,[21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…More than 10 types of HAdV involved common ocular infections, among which 7,8,11,14,19,22,37,42,48,53,54, 56, and 64 are associated with acute conjunctivitis. Of these, HAdV-8, -19 and -37 cause a more severe form of epidemic keratoconjunctivitis (EKC) [5,7,[13][14][15][16][17][18][19]. In addition, acute hemorrhagic conjunctivitis (AHC) [20][21][22] is caused by enterovirus type 70, human coxsackievirus A24 variant (CVA24v), and HAdV-11.…”
Section: Introductionmentioning
confidence: 99%